2018
DOI: 10.12691/jfnr-6-7-6
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Efficacy of Two Extraction Techniques from <i>Crithmum maritimum</i> and<i> Salicornia europaea</i>

Abstract: The aim of this work was to study the characteristics of the extracts from two halophytes, sea fennel (Crithmum maritimum L.) and marsh samphire (Salicornia europaea L.) that naturally grow on the Mediterranean coast, by using ultrasound-assisted extraction (UAE) and supercritical fluid extraction (SFE). Best conditions for UAE were found at temperature 50°C, 20 min extraction time, 1:30 ratio solid:solvent and 40% (v/v) ethanol concentration. For SFE best conditions were at 50°C and 300 bar pressures with 40%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 38 publications
5
17
2
Order By: Relevance
“…Results showed that a lower TPC value was observed in the oven-dried extract (7.41 mg GAE/g) than in the fresh and freeze-dried plant extract (8.64 and 9.74 mg GAE/g dw, respectively). The TPC values from the freeze-dried extract are also in accordance to data already reported (7.03 to 12.09 mg GAE/g dw) [ 10 ] and values for other species of freeze-dried Salicornia , namely Salicornia europaea (5.6 to 9.30 mg GAE/g dw) [ 119 ]. In contrast, studies on oven-dried S. ramosissima reported higher TPC values than the one reported in this work (27.44 to 33.00 mg GAE/g dw) [ 7 , 15 ].…”
Section: Resultssupporting
confidence: 89%
“…Results showed that a lower TPC value was observed in the oven-dried extract (7.41 mg GAE/g) than in the fresh and freeze-dried plant extract (8.64 and 9.74 mg GAE/g dw, respectively). The TPC values from the freeze-dried extract are also in accordance to data already reported (7.03 to 12.09 mg GAE/g dw) [ 10 ] and values for other species of freeze-dried Salicornia , namely Salicornia europaea (5.6 to 9.30 mg GAE/g dw) [ 119 ]. In contrast, studies on oven-dried S. ramosissima reported higher TPC values than the one reported in this work (27.44 to 33.00 mg GAE/g dw) [ 7 , 15 ].…”
Section: Resultssupporting
confidence: 89%
“…Chikhi et al [ 47 ] reported that the aqueous extract of Atriplex halimus has a phenolic content of 12.4 mg GAE/g extract, and Kim et al [ 48 ] reported that the aqueous extract of Salicornia europaea contains 11.6 mg QE/g extract. ABTS scavenging capacity of SADE is similar to that of S. europea originating from Italy (ABTS = 15.1 mg TE/g) reported by Costa et al [ 49 ]. Halophyte plant extracts are characterized by promising in vitro antioxidant activities, as reported by many authors [ 19 , 22 , 50 ].…”
Section: Resultssupporting
confidence: 84%
“…However, there are studies that have generically examined the content of phenolic compounds in Salicornia and other halophytic plants. In a work by Cristina Costa et al [50] aimed to test the extraction efficacy with different ethanol concentrations in S. europaea, total polyphenols were between 1.3 to 9.3 mg GAE/g DW; these results are in the same range as those of our work, despite the adoption of different extraction techniques. Similar results were found in S. europaea extracts collected from different regions in the southeastern coast of Tunisia (Gabés and Boughrerra) [23], demonstrated that Salicornia leaves showed a high content of secondary metabolites.…”
Section: Bioactive Compounds and Antioxidant Capacity Of Salicorniasupporting
confidence: 81%